124
Chapter 4
13.
y
=
f
−
1
(
x
),
x
=
f
(
y
) =
y
5
,
y
=
x
1
/
5
=
f
−
1
(
x
)
14.
y
=
f
−
1
(
x
),
x
=
f
(
y
) = 6
y
,
y
=
1
6
x
=
f
−
1
(
x
)
15.
y
=
f
−
1
(
x
),
x
=
f
(
y
) = 7
y
−
6,
y
=
1
7
(
x
+ 6) =
f
−
1
(
x
)
16.
y
=
f
−
1
(
x
),
x
=
f
(
y
) =
y
+ 1
y
−
1
,
xy
−
x
=
y
+ 1, (
x
−
1)
y
=
x
+ 1,
y
=
x
+ 1
x
−
1
=
f
−
1
(
x
)
17.
y
=
f
−
1
(
x
),
x
=
f
(
y
) = 3
y
3
−
5,
y
=
3
(
x
+ 5)
/
3 =
f
−
1
(
x
)
18.
y
=
f
−
1
(
x
),
x
=
f
(
y
) =
5
√
4
y
+ 2,
y
=
1
4
(
x
5
−
2) =
f
−
1
(
x
)
19.
y
=
f
−
1
(
x
),
x
=
f
(
y
) =
3
√
2
y
−
1,
y
= (
x
3
+ 1)
/
2 =
f
−
1
(
x
)
20.
y
=
f
−
1
(
x
),
x
=
f
(
y
) =
5
y
2
+ 1
,
y
=
5
−
x
x
=
f
−
1
(
x
)
21.
y
=
f
−
1
(
x
),
x
=
f
(
y
) = 3
/y
2
,
y
=
−
3
/x
=
f
−
1
(
x
)
22.
y
=
f
−
1
(
x
),
x
=
f
(
y
) =
2
y,
y
≤
0
y
2
,
y >
0
,
y
=
f
−
1
(
x
) =
x/
2
,
x
≤
0
√
x,
x >
0
23.
y
=
f
−
1
(
x
)
, x
=
f
(
y
) =
5
/
2
−
y,
y <
2
1
/y,
y
≥
2
,
y
=
f
−
1
(
x
) =
5
/
2
−
x,
x >
1
/
2
1
/x,
0
< x
≤
1
/
2
24.
y
=
p
−
1
(
x
),
x
=
p
(
y
) =
y
3
−
3
y
2
+ 3
y
−
1 = (
y
−
1)
3
,
y
=
x
1
/
3
+ 1 =
p
−
1
(
x
)
25.
y
=
f
−
1
(
x
),
x
=
f
(
y
) = (
y
+ 2)
4
for
y
≥
0,
y
=
f
−
1
(
x
) =
x
1
/
4